Tailored Mesoporous Silica Nanoparticles for Controlled Drug Delivery: Platform Fabrication, Targeted Delivery, and Computational Design and Analysis - She, Xiaodong; Chen, Lijue; Yi, Zhifeng; Li, Chengpeng; He, Canzhong; Feng, Chunfang; Wang, Tao; Shigdar, Sarah; Duan, Wei; Kong, Lingxue (Mini Reviews in Medicinal Chemistry, 2018)
Mesoporous silica nanoparticles (MSNs) are exceptionally promising drug carriers for controlled drug delivery systems because their morphology, pore structure, pore volume and pore size can be well tailored to obtain certain drug release profiles. Moreover, they possess the ability to specifically transport and deliver anti-cancer drugs when targeting molecules are properly grafted onto their surface. MSNs based drug delivery systems have the potential to revolutionize cancer therapy. This review provides a comprehensive overview of the fabrication, modification of MSNs and their applications in tumour-targeted delivery. In addition, the characterization and analysis of MSNs with computer aided strategies were described. The existing issues and future prospective concerning the applications of MSNs as drug carriers for controlled drug delivery systems were discussed.
Keywords: mesoporous silica nanoparticles (MSN)